2021
DOI: 10.11130/jei.2021.36.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Is Trade in COVID-19 Products in ASEAN Economies a Building or Stumbling Block?

Abstract: Stumbling blocks to regional integration continue to pose a serious threat to the World Trade Organization (WTO), particularly during the COVID-19 pandemic. This study aims to examine the effect of regional economic integration on trade in COVID-19 products for Association of Southeast Asian Nations (ASEAN) countries using quarterly data for 2010-2020. A panel data model is estimated using the Poisson pseudo-maximum likelihood approach to address zero trade values, cross-sectional dependence, and heterogeneity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Meanwhile, Ugurlu and Jindřichovská [2022] identified robust trade relationships with major European economies, and Georgopoulos [2020] noted the continued effectiveness of the European single market in agri-food trade among member states. Uttama [2021] established positive and substantial trade in COVID-19 related products within ASEAN economies, attributed to their productive and absorptive capacities, as well as their similar size and per capita income. Khorana et al 18 explored trade effects in the CIS, revealing comparatively stronger trade relations for higher-income countries.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Meanwhile, Ugurlu and Jindřichovská [2022] identified robust trade relationships with major European economies, and Georgopoulos [2020] noted the continued effectiveness of the European single market in agri-food trade among member states. Uttama [2021] established positive and substantial trade in COVID-19 related products within ASEAN economies, attributed to their productive and absorptive capacities, as well as their similar size and per capita income. Khorana et al 18 explored trade effects in the CIS, revealing comparatively stronger trade relations for higher-income countries.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The outcomes of a case study on bilateral trade in COVID-19 products by Uttama (2021) revealed that the ASEAN trading bloc is a deterrent to the rules-centred multilateral trading system of the World Trade Organization (WTO). The results of Uttama (2021) suggest that the productive competence of the home country, the absorptive capability of the host country, the similarity in member size and per capita income and the degree of remoteness of member countries have positive and significant relationships with trade in COVID-19 products within the Association of Southeast Asian Nations (ASEAN).…”
Section: Empirical Understandingsmentioning
confidence: 99%
“…The outcomes of a case study on bilateral trade in COVID-19 products by Uttama (2021) revealed that the ASEAN trading bloc is a deterrent to the rules-centred multilateral trading system of the World Trade Organization (WTO). The results of Uttama (2021) suggest that the productive competence of the home country, the absorptive capability of the host country, the similarity in member size and per capita income and the degree of remoteness of member countries have positive and significant relationships with trade in COVID-19 products within the Association of Southeast Asian Nations (ASEAN). In terms of COVID-19 vaccine production and distribution, Sorescu et al (2021) acknowledged the strength of trade as a mechanism of distributing COVID-19 vaccines and called for the preservation of market openness through diminishing tariffs, rationalising trade-related procedures at and prior to points of entry while simultaneously necessitating enhanced management of logistical processes.…”
Section: Empirical Understandingsmentioning
confidence: 99%
“…Hölscher et al (2010) also studied the competitiveness between India and China in relation to international trade. The study also examines how regional economic integration influences trade in COVID-19 products, and it identifies a range of factors that are crucial for positive trade between the two countries (Uttama, 2021). Khan and Ahmad (2017) analysed the export pattern and competitiveness of India-China in global and bilateral market.…”
Section: Theoretical Frameworkmentioning
confidence: 99%